2012
DOI: 10.1039/c2an16193a
|View full text |Cite
|
Sign up to set email alerts
|

Microwave high performance liquid chromatography with UV-visible detection. Application to vitamins determination

Abstract: The present work describes the first attempt to use microwave reversed phase high performance liquid chromatography (MW-HPLC) to carry out the separation of organic compounds. Biotin and riboflavin were selected for the characterization of the new separation technique. Additional vitamins (nicotinamide, pyridoxine and thiamine) were used as reference compounds. In order to perform the separation, a chromatographic column was placed inside a domestic microwave oven in a hanging position. The column particular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…This fact indicates that equilibrium conditions should have been reached inside of the HPLC column. Previous studies using microwave radiation to assist an HPLC separation also showed a similarthis trend (Carballo et al, 2015;Terol et al, 2012). It should be mentioned that, although the MW radiation was quickly absorbed by the mobile phase, moderate heating inside of the column was produced in this application.…”
Section: Optimisation Of the Mw-hplc-elsd System For Separation Of Tgssupporting
confidence: 57%
See 4 more Smart Citations
“…This fact indicates that equilibrium conditions should have been reached inside of the HPLC column. Previous studies using microwave radiation to assist an HPLC separation also showed a similarthis trend (Carballo et al, 2015;Terol et al, 2012). It should be mentioned that, although the MW radiation was quickly absorbed by the mobile phase, moderate heating inside of the column was produced in this application.…”
Section: Optimisation Of the Mw-hplc-elsd System For Separation Of Tgssupporting
confidence: 57%
“…This significant heating was due to the composition of the mobile phase. Additionally, a 40 and % reduction in peak width was registered for riboflavin and biotin, respectively (Terol et al, 2012) (Terol et al, 2012a). In a different application involving separation of fat-soluble vitamins, the application of MW radiation at 170 W resulted in a 36 % shortening in analysis time with respect to conventional HPLC.…”
Section: Comparison Of Chromatographic Tgs Separation Obtained With Cmentioning
confidence: 99%
See 3 more Smart Citations